2006
DOI: 10.1007/s10488-006-0051-5
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Case Management: A Critical Re-Appraisal of the Scientific Evidence for Effectiveness

Abstract: Intensive Case Management (ICM) is widely claimed to be an evidence-based and cost effective program for people with high levels of disability as a result of mental illness. However, the findings of recent randomized controlled trials comparing ICM with 'usual services' suggest that both clinical and cost effectiveness of ICM may be weakening. Possible reasons for this, including fidelity of implementation, researcher allegiance effects and changes in the wider service environment within which ICM is provided,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 39 publications
0
16
0
2
Order By: Relevance
“…27,28 ACT interventions with higher fidelity to the ACT model have been shown to result in stronger outcomes, with the exception of strict adherence to the low staff-to-patient ratios, which may be a somewhat more flexible criterion. 29,30 ACT interventions also appear to be most successful among populations with high rates of hospitalization.…”
Section: Port Psychosocial Treatment Recommendationsmentioning
confidence: 99%
“…27,28 ACT interventions with higher fidelity to the ACT model have been shown to result in stronger outcomes, with the exception of strict adherence to the low staff-to-patient ratios, which may be a somewhat more flexible criterion. 29,30 ACT interventions also appear to be most successful among populations with high rates of hospitalization.…”
Section: Port Psychosocial Treatment Recommendationsmentioning
confidence: 99%
“…Numerous controlled studies document the effectiveness of ACT in the treatment of consumers with extensive histories of psychiatric hospitalizations (Baronet & Gerber, 1998;Bedell, Cohen, & Sullivan, 2000;Bond, Drake, Mueser, & Latimer, 2001;Gorey et al, 1998;Herdelin & Scott, 1999;Latimer, 1999;Marshall & Creed, 2000;Ziguras & Stuart, 2000), although some recent studies with strong comparison conditions (e.g., Essock et al, 2006) and studies in the United Kingdom (Fiander et al, 2003;King, 2006) have found that intensive case management programs can be as effective as ACT. ACT is remarkable for the articulation of its structural and functional features (McGrew & Bond, 1995), as well as for having a widely-used fidelity scale to assess a teamÕs adherence to an ideal ACT model for staffing and services (Teague, Bond, & Drake, 1998).…”
Section: Act Effectiveness: the Evidence Base For The Practicementioning
confidence: 99%
“…This has implications for the effectiveness of services, as ACT at full fidelity has been shown to increase the likelihood of clients to remain in contact with services, reduce hospitalizations, improve accommodation and employment outcomes, and have higher patient satisfaction ratings (Marshall and Lockwood 2000). However, differences between ACT and case management have been challenged in recent literature (King 2006), which may, in part, explain why there were not significant differences between the regions in terms of psychiatric hospitalizations, accommodation and employment despite differences in fidelity. North Carolina rural teams reported visiting clients on average once a week, while the urban team had more frequent visits.…”
Section: Discussionmentioning
confidence: 99%